Incidence and risk of short episodes of atrial fibrillation detected with 14 days of continuous electrocardiographic monitoring. (25th November 2020) - McIntyre, W.F; Wang, J; Connolly, S.J; Van Gelder, I.C; Lopes, R.D; Gold, M.R; Hohnloser, S.H; Lau, C.P; Israel, C.W; Benz, A.P; Wong, J.A; Conen, D; et al.
Abstract: Background: There is widespread interest in population-based screening for atrial fibrillation (AF). However, there is debate regarding the optimal screening method and duration. Objectives: To estimate the incidence of short-duration AF detected by a single continuous 14-day electrocardiographic (ECG) monitor in older individuals without prior AF and to estimate the risk of ischemic stroke or systemic embolism associated with these episodes. Methods: Pacemaker and defibrillator electrograms were reviewed from a cohort of individuals ≥65 years old, with a history of hypertension, but no prior AF. For each participant, we simulated a continuous 14-day ECG monitor by randomly selecting a 14-day window in the 6 months following enrolment and measured the total AF burden during that period. We repeated random sampling 1000 times to ensure a robust estimate of the likelihood of capturing AF in a single 14-day period. We used Cox proportional hazards models adjusted for CHA2DS2-VASc score to estimate the risk of ischemic stroke or systemic embolism associated with different burdens of AF. Results: Among 2470 participants with at least 6 months of follow-up, the mean CHA2DS2-VASc score was 4.0±1.3. The proportion of participants with an AF burden of >6 min on a single 14-day monitor was estimated as 3.1%, while the proportion with burdens of >15 min and >30 min were 2.9% and 2.6%, respectively. Over a mean follow-up of 2.5 years, 44 participants had an ischemic stroke or systemic embolism; the rate among patients with an AF burden ≤6 mins was 0.70%/year. An AF burden >6 min was associated with an increased risk of stroke or systemic embolism (2.2%/year, HR 3.0; 95% CI 1.3–5.7), as were burdens >15 min (2.4%/year; HR 3.3; 95% CI 1.4–6.4) and >30 min (2.6%/year HR 3.5; 95% CI 1.5–6.7). Conclusion: Approximately 3% of individuals aged 65 years and older and with hypertension may have previously undiagnosed asymptomatic AF detected by a single 14-day continuous ECG monitor. As little as 6 minutes of AF may be associated with an increased risk of stroke. Randomized clinical trials are required to definitively assess screening in this population. Funding Acknowledgement: Type of funding source: None